Effect of Team Cooperation and Work Commitment on Employee Performance of PT. Ambassador of Sarana Jaya Seventeen Semarang - Savira, Nava Bella; Juniarto, Galuh (Untag Business and Accounting Review, 2022)
Many factors can affect employee performance such as teamwork and work commitment. This study aims to analyze the effect of teamwork and work commitment on employee performance. The population in this study was all employees and the sample in this study were all employees of 50 respondents at PT. Duta Sarana Jaya Seventeen Semarang. Therefore, this study uses a saturated sampling technique, which means that the entire population is used as a sample or respondent. The analytical tool used in this study uses multiple linear regression analysis and the application uses SPSS ver. 20. Based on the analysis results show that teamwork has a positive and significant effect on employee performance, and work commitment has a positive and significant effect on employee performance.